The vitamin D metabolite ratio (VMR) as a predictor of functional biomarkers of bone health. (31st March 2017) - Aloia, John; Fazzari, Melissa; Shieh, Albert; Dhaliwal, Ruban; Mikhail, Mageda; Hoofnagle, Andrew N.; Ragolia, Lou
Summary: Context: The vitamin D metabolite ratio (VMR) (serum 24, 25(OH)2 D3 /25(OH)D3 ) has been proposed as a biomarker of vitamin D sufficiency to replace serum 25(OH)D. Objective: To examine the relationships of 24, 25(OH)2 D3 and VMR to functional biomarkers of bone health following vitamin D supplementation. Setting: An ambulatory research centre. Design: Serum from a previous research study of dose response of PTH, calcium absorption and bone turnover to vitamin D supplementation was analysed for vitamin D metabolites (25(OH)D, 24, 25(OH)2 D3 ). Outcome: The relationship of serum 24, 25(OH)2 D3 and VMR to calcium absorption, PTH and bone turnover markers was examined. Results: Although there were strong correlations of serum 25(OH)D with 24, 25(OH)2 D3 and free 25(OH)D, its correlation with VMR was lower. After vitamin D supplementation, the change in 25(OH)D, 24, 25(OH)2 D3 and VMR was associated with the change in calcium absorption, PTH and CTX. The correlation of the change in PTH with the change in metabolites was the lowest for VMR. Moreover, estimated dose response for standardized values of vitamin D metabolites showed a beta‐coefficient for VMR that was significantly less in magnitude compared to other metabolites. Conclusion: Serum 24, 25(OH)2 D3 is closely associated with the dose response of serum 25(OH)D to vitamin D supplementation. However, the VMR does not appear to be equivalent to either of these metabolites in its response to increasing vitamin D intake or its association with PTH. It is unlikely that VMR will replace 25(OH)D as a biomarker for vitamin D sufficiency.